The role of regulatory oversight in improving the quality of work - Chibani, Fouzia (Journal of Human Sciences, 2022)
This study came to clarify the status of work quality and the role of oversight in improving it, and perhaps the main objective of this study is to know whether organizational control has a role in improving work quality, that is, does it achieve effectiveness and contribute to the development and improvement of working performance in organizations, and several studies have shown that Control affects the process of improving the quality of work and has a significant and effective role in the institution, and that the determinants of quality affect the improvement of the performance of workers in the institution. Since work is associated with oversight, we see that a slight change in the path leads organizations to decay, and this is what organizations should not overlook. The more effective the organizational control and with good standards, the performance is distinctive and effective, and the result is a healthy and healthy professional life for all workers.